How 'transformative' is energy storage? Insights from stakeholder perceptions in Ontario. (October 2018) - Gaede, James; Rowlands, Ian H.
Abstract: 'Energy storage' comprises a range of technologies of varying maturity and cost-effectiveness, which are increasingly considered to be an important part in building the electricity system of the future. As with any potentially transformative technology, there remain questions of how, and under what context, electricity system stakeholders (new and old) will perceive the technology. Our interest in this paper is to identify and assess the political and sociotechnical system factors that stand to shape the extent to which energy storage can be considered transformational. To do so, we investigate the transformative potential of storage in Ontario, Canada, based on interviews with key electricity system stakeholders. We find that the transformative potential of energy storage is by no means preordained, and is instead intimately intertwined with the complex interactions between actors and institutional factors in each and across three electricity system subsectors.